A review of an Islamic financial dictionary - Ali, Antar Fuad; Shunmugam, Krishnavanie; Saleh, Abdulmajid Obaid Hasan; Saleh, Sukainah Hasan (Al-Hikmah Research & Publication Center, 2021)
Islamic banking has seen a lot of progress and attracted global attention. It has also attracted multiple studies and research. Lexicography has been part of the areas touched upon by research to provide the necessary tools to comprehend terms and concepts related to Islamic financial terminology. Having said that, the inadequacy of the studies and works has shown an area that awaits further improvement and investigation. Thus, the current paper aims to provide a brief review of a dictionary called Dictionary of Financial and Economic Terms in the Register of Jurists by Nazih Hammad (2008). The introductory matter, content, and structure are analysed in comparison to lexicographic works. Finally, recommendations are made to improve similar works.